VARIASI LATIHAN UNTUK MENINGKATKAN HASIL PUKULAH FOREHAND BULUTANGKIS PADA ATLET PEMULA - Muhammad Jalaluddin; Mimi Haetami; Uray Gustian (Universitas Tanjungpura, 2021)
AbstractBadminton is a sport that requires basic technical skills, one of which is the forehand. Forehand technique must be mastered so that badminton can run smoothly and can score points. However, many athletes are still not good at forehand strokes so that when they do forehand strokes it is less effective. For this reason, a focused and precise training is needed, namely by using a variety of exercises to improve the forehand stroke. The purpose of this study was to determine the results of beginner forehand training using variations of badminton forehand stroke training. The method used was an experimental model with a preexperimental design one group pretest-posttest design. The population in this study were badminton players PB SATU al-huda pontianak, with a sample size of 12 athletes. Based on data analysis, there was an increase in the ability of the forehand stroke. The results obtained were an average pretest score of 66.5 and posttest 81.8 and an effect size test of 6.5. The conclusion in this study is that there is an increase in the forehand ability of the novice athletes PB SATU al-huda Pontianak.Keywords: Badminton, Exercise Variation, Forehand Stroke